2013
DOI: 10.1111/ggi.12083
|View full text |Cite
|
Sign up to set email alerts
|

Predicting clinical instability of older patients in post‐acute care units: A nationwide cohort study

Abstract: Approximately 13% of PAC patients might experience acute ward readmissions, and nearly 90% of them are caused by medical conditions. Poor cognitive function is a significant predictive factor for clinical instability in PAC, which deserves more clinical attention for all PAC patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 40 publications
1
8
0
1
Order By: Relevance
“…The high pooled prevalence of malnutrition and risk of malnutrition according to MNA confirm earlier findings from a meta-analysis with slightly higher pooled prevalence (95% CI) of 29% (22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37) for malnutrition and 49% (42)(43)(44)(45)(46)(47)(48)(49)(50)(51)(52)(53)(54)(55) for risk of malnutrition [83]. However, heterogeneity was high, which limits the interpretation of these results.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…The high pooled prevalence of malnutrition and risk of malnutrition according to MNA confirm earlier findings from a meta-analysis with slightly higher pooled prevalence (95% CI) of 29% (22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37) for malnutrition and 49% (42)(43)(44)(45)(46)(47)(48)(49)(50)(51)(52)(53)(54)(55) for risk of malnutrition [83]. However, heterogeneity was high, which limits the interpretation of these results.…”
Section: Discussionsupporting
confidence: 81%
“…The total Functional Independence Measure (FIM) score had a broad range between 56 (43.5) [36] and 88.5 (41.0) points [63] (median (IQR). The Katz ADL score and the Lawton Brody IADL score ranged from 2.6 ± 1.9 [78,80] to 3.9 ± 1.9 points [35] and from 1.7 ± 1.8 [55] to 4.8 ± 2.6 points [80] (mean ± SD), respectively, indicating reduced status of ADL and IADL.…”
Section: Functional Statusmentioning
confidence: 99%
“…46) We found that only approximately 12.9% of the patients are transferred to the acute ward, which is better than the figures for many European and American countries, and the reason for hospitalization is usually infectious disease. 46) Taiwan's National Health Insurance began implementing post-acute care services for stroke patients in 2014. In the community hospital post-acute care model for stroke patients, personnel provide high-intensity rehabilitation training based on the patient's Comprehensive Geriatric Assessment results, and patients are accepted based on the occurrence of stroke and a modified Rankin Scale Score of 2-4, indicating the patient's functional status as determined by the acute hospital diagnosis.…”
Section: Effectiveness and Quality Of Post-acute Care In Taiwanmentioning
confidence: 55%
“…No estudo realizado por Lee et al 12 foi utilizada a MAN como instrumento avaliador, atualmente considerada o melhor método de triagem e avaliação nutricional em idosos, por abranger as particularidades dessa população. O instrumento engloba antropometria, avaliação dietética, avaliação clínica global e autopercepção de saúde e do estado nutricional, podendo ser utilizada tanto para triagem como para avaliação nutricional.…”
Section: Discussionunclassified